Politics in contemporary Southeast Asia authority, democracy and political change - Kingsbury, Damien (Routledge, an imprint of the Taylor & Francis Group, 2017)
The countries of Southeast Asia continue to change, evolve and chart courses that sometimes leave outside observers puzzled. Politics in Contemporary Southeast Asia thoroughly assesses the political challenges and changes faced by the countries of Southeast Asia in the 21st century. Focusing on political processes throughout, Kingsbury introduces readers to the challenges of representation and accountability of the regional governments, degrees of good governance and transparency, and the role of elites and militaries in shaping or determining political outcomes. This book provides: A comprehensive, but accessible, introduction to political change and processes in Southeast Asia. Analytic criteria for assessment of case studies. Detailed country-specific surveys. Information based on extensive research on, and work in, the region. Providing cutting-edge coverage of South Asian politics in all regions, this highly accessible and comprehensive book is suitable for undergraduate and postgraduate courses on South East Asian Studies, Asian Politics, and Democratization